Performance of a New Fibrin Monomer Assay to Exclude Deep Vein Thrombosis in Symptomatic Outpatients - Caliezi, Christoph; Fünfsinn, Nadja; Mauron, Thomas; Baumgartner, Iris; Sulzer, Irmela; Ulrich, Martin; Cottier, Christoph; Biasiutti, Franziska Demarmels; Lämmle, Bernhard; Wuillemin, Walter A. (Thrombosis and Haemostasis, 1999)
In this study we prospectively assessed the reliability of a new fibrin monomer assay in 106 outpatients with clinically suspected deep venous thrombosis of the lower limb. According to the results of the objective tests and using different cut-off points we calculated the sensitivity, specificity and negative predictive value of the fibrin monomer assay. The prevalence of deep vein thrombosis was 44.3% (31.1% proximal, 13.2% distal). Using a cut-off level of plasma fibrin monomer of 3.5 μg/ml, a sensitivity, specificity and negative predictive value of 100% (95% CI: 94-100%), 35.6% (95% CI: 23-48%) and 100% (95% CI: 86-100%), respectively, were obtained. The exclusion rate was 19.8% (95% CI: 12-27%) of all referred patients. These accuracy indices compared favourably with the respective results of a routine D-dimer ELISA used for comparison. Conclusion: This new fibrin monomer assay appears to be a reliable method for the exclusion of deep vein thrombosis in symptomatic outpatients.